A description of manual wheelchair skills training curriculum in entry-to-practice occupational and physical therapy programs in Canada. (September 2015) - Best, Krista L.; Miller, William C.; Routhier, François
Abstract Purpose: To describe the curriculum for manual wheelchair (MWC) skills training in entry-to-practice occupational (OT) and physical therapy (PT) programs in Canada. Methods: An online survey was sent to 28 directors of entry-to-practice OT and PT programs in Canadian universities. Responses were solicited from individuals who could report about wheelchair skills training. Fourteen survey questions asked about: (1) demographic information, (2) specific curriculum content for MWC skills training, (3) teaching methods used, (4) instructional methods and estimated time used to teach MWC skills and (5) whether validated wheelchair skills training programs were used in curriculum development. Results: Responses received from 21/28 programs, (OT-11/14; PT-10/14). About 16 of 21 programs included curriculum for MWC skills training. Informal hands-on instruction was the most common method used for teaching wheelchair skills (13/21), while multiple lectures were used the least (5/21). Only 8/21 used a validated wheelchair skills training program in curriculum development. Conclusion: Despite the public availability of a validated wheelchair skills program, there is little use of the program in entry-to-practice curriculum. Integrating online training programs into existing curricula or the development of post-professional training modules may help clinicians to better accommodate the mobility needs of the substantially increasing population with disabilities. Implications for Rehabilitation Current clinical curriculum includes basic wheelchair skills training, but not necessarily training in the advanced wheelchair skills that are needed for optimal wheelchair mobility. There is evidence for a standardized approach for providing wheelchair skills training, that may be administered through curriculum, online or through post-graduate training modules.